Pengaruh Kompensasi, Motivasi Kerja, Dan Lingkungan Kerja Terhadap Kinerja Karyawan(Studi Empiris Pada Karyawan Bagian Akuntansi Pt. Jamu Air Mancur Karanganyar) - Pratama, Naofal Yudha, Dra. Mujiyati, M.Si (2017)
This study aims to determine the effect of Compensation, Work Motivation and Work Environment on Employee Performance. The empirical study on the employees of the accounting department of PT. Jamu Air Mancur Karanganyar. The sampling method in this study using saturated sample. The total number of respondents who participated were at 44 employees. Analyzed using Multiple Linear Regression using SPSS 17. Based on these results show that the variable compensation, motivation, and the Working Environment influence on employee performance. Keywords: compensation, work motivation, work environment, and employee performance.